Fighting chance : a Gregor Demarkian novel - Haddam, Jane, 1951-2019- (Haddam, Jane, 1951-2019- Gregor Demarkian books., 2014)
When his best friend, parish priest Tibor Kasparian, is wrongly arrested for murder, a distraught Gregor Demarkian breaks his personal rules about consulting in his determination to uncover the truth.